Gordon Matta-Clark - Open House - Davila, Thierry 1963-; Costes, Sophie; Yee, Lydia ca. 20./21.Jh (Mamco Genève, 2019)
Open House / Thierry Davila -- Histoire d'une construction éphémère hybride / Sophie Costes -- Danser sur l'architecture / Lydia Yee
Includes bibliographical references (page 141)
Keywords: Matta-Clark, Gordon -- 1943-1978 -- Open House; Geschichte 1972; Installation -- Kunst; Matta-Clark, Gordon / 1943-1978 / Open House; Installations (Art) / Switzerland / Geneva